Toward an environmentally sustainable city in the light of industrial revolution 4.0: A case study of Ho Chi Minh City - DUNG, Tran Viet (Institutional Knowledge at Singapore Management University, 2022)
Like other large cities in ASEAN, Vietnamese cities have been facing serious urban environment problems such as air pollution, land degradation, weak water drainage and lack of green spaces. These problems are caused by unsustainable patterns of development. City governments have failed to coordinate and integrate city planning consistently. Trends show that governments prefer to take short-term economic profit rather than focus on environmental protection.